Integrative Analysis of the Expression Levels and Prognostic Values for NEK Family Members in Breast Cancer - Gao, Wen-Liang; Niu, Lei; Chen, Wei-Ling; Zhang, Yong-Qu; Huang, Wen-He (Frontiers in Genetics, 2022)
Background: In the latest rankings, breast cancer ranks first in incidence and fifth in mortality among female malignancies worldwide. Early diagnosis and treatment can improve the prognosis and prolong the survival of breast cancer (BC) patients. The NIMA-related kinase (NEK), a group of serine/threonine kinase, is a large and conserved gene family that includes NEK1-NEK11. The NEK plays a pivotal role in the cell cycle and microtubule formation. However, an integrative analysis of the effect and prognosis value of NEK family members on BC patients is still lacking. Methods: In this study, the expression profiles of NEK family members in BC and its subgroups were analyzed using UALCAN, GEPIA2, and Human Protein Atlas datasets. The prognostic values of NEK family members in BC were evaluated using Kaplan-Meier plotter. Co-expression profiles and genetic alterations of NEK family members were analyzed using the cBioPortal database. The function and pathway enrichment analysis of the NEK family were performed using the WebGestalt database. The correlation analysis of the NEK family and immune cell infiltration in BC was conducted using the TIMER 2.0 database. Results: In this study, we compared and analyzed the prognosis values of the NEK. We found that NEK9 was higher expressed in normal breast tissues than BC, and NEK2, NEK6, NEK11 were significantly higher expressed in BC than adjacent normal tissues. Interestingly, the expression levels of NEK2, NEK6, and NEK10 were not only remarkably correlated with the tumor stage but also with the molecular subtype. Through multilevel research, we found that high expression levels of NEK1, NEK3, NEK8, NEK9, NEK10, and NEK11 suggested a better prognosis value in BC, while high expression levels of NEK2 and NEK6 suggested a poor prognosis value in BC. Conclusions: Our studies show the prognosis values of the NEK in BC. Thus, we suggest that NEK may be regarded as novel biomarkers for predicting potential prognosis values and potential therapeutic targets of BC patients.